The Pick-and-Roll in Basketball From Deep Interviews of Elite Coaches: A Mixed Method Approach From Polar Coordinate Analysis - Nunes, Hermilo; Iglesias, Xavier; Del Giacco, Luca; Anguera, M. Teresa (Frontiers in Psychology, 2022)
Pick and roll is the most widespread cooperative action among high-level basketball teams and the most applied strategy by coaches to gain an advantage over the rival team. During the pick and roll, opposing teams perform antagonistic actions based on goals that are expressed into offensive and defensive tactics, respectively. The aim of this study is to examine the approaches of high-level coaches about the offensive and defensive dynamics emerging in the matches of a basketball elite team during an entire season of the Spanish ACB League. To this end, we used a mixed methods approach based on the systematic observation of verbatim transcripts of interviews conducted with six high-level coaches about the pick and roll dynamics that emerged in the matches of the Unicaja Málaga team during an entire season of ACB League. The observational design was nomothetic, punctual, and multidimensional. The choice of this methodology is justified since we developed an ad hoc indirect observation tool to evaluate the coaches’ perspective on this dynamic. Once the intra-observer reliability for the instrument was confirmed, we performed polar coordinate analysis to identify the significant relationships between the coaches’ evaluations and the offensive and defensive pick and roll elements that supported such verbal behaviors. The results highlight the presence of various offensive and defensive aspects of pick and roll (n=2224) emerging in the Unicaja team that were significantly associated with the positive and negative evaluations of coaches. The interview confirms that Coach 1 and his staff were less confident in the options that pick and roll offers, which is also reflected in the record of screens made and simulated compared to Coach 3. This study shows that the application of mixed methods, through the analysis of the polar coordinate of the coding carried out on the responses of a systematized interview, has proven to be an effective strategy in obtaining relevant information on the expert knowledge of the elite coaches on the influence of the pick and roll in tactical actions in basketball.